Peculiarities of indicators of the respiratory system in women at rest and their changes during the burning of the next cigarette - Shevchuk, Tatiana Ya.; Aponchuk, Lyudmila S.; Pikalyuk, Vasyl S.; Olishkevich, Oksana O. (National Pirogov Memorial Medical University, 2022)
One of the important problems facing modern society is the increase in the number of people with various types of addictions, the most common of which is smoking. Smoking and its medical-demographic and economic consequences are in the circle of scientific interests of many domestic and foreign scientists. That is why the aim of the scientific article is to study the peculiarities of the state of the respiratory system in women at rest and during the burning of another cigarette. The study was conducted in the Laboratory of Medical and Biological Monitoring and Public Health at the Department of Human and Animal Physiology, Faculty of Biology and Forestry, Lesya Ukrainka Volyn National University for 60 women aged 17-21. At the first stage of the study, absolute anthropometric indicators were measured, such as height, weight, chest circumference. In the second stage women were interviewed on the Fagerström test. According to its results, the study is divided into 3 groups: Group I - women who have a history of smoking more than 3 years, burn more than 10 cigarettes per day and have a high level of dependence, Group II - women who have a history of smoking 1-3 years, up to 10 cigarettes are smoked per day and have a low and medium level of dependence, Group III - (control) women who do not smoke. The next stage of the study involved a functional diagnosis of the external respiratory system in women at rest and 15 minutes after smoking a cigarette using the functional method of pneumotachography (PTG). Registration and analysis of relevant indicators was carried out using a diagnostic automated complex "Cardio+". Statistical data processing was performed using generally accepted methods of variation statistics (because the distribution of the results was normal) using MS Excel 2007 software. This article presents a study of the state of external respiration at rest and 15 minutes after burning another cigarette, which revealed the negative effects of smoking on the respiratory system of women who smoke. The study made it possible to make a detailed analysis of indicators of respiratory function in women aged 17-21 years, smokers and compare them with non-smokers. Based on the obtained results, it was found that in women smokers (groups I and II) there is a significant decrease in volume (FVC, VC, FEV1) indicators of external respiration, as well as the Tiffeneau- Pinelli test at p<0.05, compared with the group of women control group both at rest and 15 minutes after firing the next cigarette. Analysis of velocity (MEF at the level of exhalation 25 %, 50 %, 75 %, PEF) of airflow through the bronchi to the lungs indicates a gradual decrease from MEF 25 % to MEF 75 % in women of the experimental groups, but a significant decrease is observed only at the level sight of 75 % in 15 min after burning of the next cigarette between I and III groups (at p<0.05). A statistically significant difference between the values of the calculated Tiffeneau-Pinelli index, which characterizes the presence of obstructive respiratory failure, in women of groups II and III both at rest and 15 minutes after burning another cigarette. Thus, a decrease in these indicators indicates the presence of bronchial obstruction of the middle and small bronchi, as well as a violation of respiratory muscle strength and bronchial patency. It has also been shown that the reactivity (reduction) of volumetric and velocity indicators of external respiration to cigarette burning was higher in the group of women who do not smoke (control).
Keywords: smoking; women-smokers; external respiration; cigarettes; reactivity; 612.2-055.2:613.81/.84